Genetics of mycobacterial adaptation to selective pressure of antituberculous compounds dissected at the in vitro and in vivo levels - Igor Mokrousov; Tatiana Vinogradova; Natalia Solovieva; Ivaylo Slavchev; Marine Dogonadze; Sergei Chekrygin; Dmitry Polev; Anna Vyazovaya; Georgi Dobrikov; Violina T. Angelova; Violeta Valcheva; Viacheslav Zhuravlev (Journal of Global Antimicrobial Resistance)
BACKGROUND: Different spontaneous mutations emerge in Mycobacterium tuberculosis and those beneficial for bacterial survival are selected leading to bacterial drug resistance, tolerance and ultimately - persistence. AIM: To study M. tuberculosis genetic variation in response to selective pressure of antibiotics and derived compounds in vivo and in vitro, to gain insight into resistance mechanisms. METHODS: C57Bl/6 mice were infected with different MDR clinical strains followed by treatment with moxifloxacin, linezolid, and bedaquiline. Bacterial isolates were recovered from the lungs of euthanized mice after 2 and 5.5 months of treatment. For in vitro study, H37Rv reference strain was cultured under elevated concentrations of new compounds, and resistant clones were subjected to whole-genome sequencing as single or pooled colonies (metagenomics-like approach). RESULTS: The complete treatment course significantly reduced the bacterial burden of the lungs of mice; no resistance mutations emerged even negligibly. The in vitro mutagenesis study revealed M. tuberculosis response to nitrofuranyl amide through multiple pathways (Rv0224c, fbiC, iniA, Rv1592c genes), reportedly counteracting oxidative and nitrosative stress. Classical mutagenesis approach revealed several genes involved in M. tuberculosis response to isoniazid derivatives: glpK frameshift mutation linked to reversible drug tolerance and nonsynonymous mutation in Rv3755c located nearby the ABC transporter/efflux genes. CONCLUSIONS: M. tuberculosis exhibited a complex multifaceted genetic response to nitrofuranyl amide and isoniazid derivatives. Nevertheless, when mice infected with various multidrug-resistant strains were treated with scientifically validated chemotherapy regimens, no new resistance mutations developed, and the treatment outcome was favorable. This indicates a promising strategy for combating drug-resistant tuberculosis.